Efficacy of sertraline in the treatment of major depressive disorder smong adult population: a systematic review - Maha, Tasfiah Tasnim (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.